Empowering Pregnant Women with Health Promotion Strategies to Prevent Chronic Energy Deficiency (CED): Systematic Review - Ratna Indriyani; Yenny Puspitasari; Novita Ana Anggraini (Universitas STRADA Indonesia, 2024)
Background: Pregnant women's nutrition is very important for the growth and development of the fetus. Nutrition for pregnant women is very important for the development and growth of the fetus. The application of the concept of a health promotion model strategy as the right strategy to improve and prevent CED is urgently needed. Purpose: To find out changes in the behavior of empowering pregnant women with a strategic model of a health promotion approach to prevent CED. Method: The method used systematic review. Articles were searched using keywords that had been determined by the researcher then the articles were extracted based on inclusion and exclusion criteria. Thus, found 7 articles suitable for analysis. Results: Changing behavior by empowering pregnant women using health promotion strategies in preventing CED has proven to be very effective. But in its application it becomes a complex thing because of the diversity of cultures in Indonesia. Conclusion: The diversity of community characteristics can affect the application of the model of empowering pregnant women in preventing CED. Several other factors such asbeliefs and environment that are understood also affect the understanding of each individual.